Evolution and depression - Donald Wittman; Nirvikar Singh (University of California, Economics Department, 2012)
The standard evolutionary explanation for depression is that being emotionally depressed is adaptive. We argue that being depressed is not adaptive (indeed, quite the opposite), but that the threat of depression for bad outcomes and the promise of pleasure for good outcomes are adaptive because they motivate people toward undertaking effort that increases fitness. We first model the optimal emotional incentive structure. We employ a principal-agent model, where the principal is the gene and the agent is the individual. The principal-agent model is a useful construct to characterize the long run tendency of evolutionary forces to reward those characteristics that increase fitness and survival of the gene. A key difference between our setup and the standard principal-agent model is that both punishment (depression) and reward (elation) have a fitness cost to the principal. We then discuss suboptimal outcomes, including bipolar disorder, unipolar depression, and lack of motivation.
Keywords: D01; D03; B52; 330; Depression; evolution; bipolar disorder; motivation; adaptation